ChemInform Abstract: A General Metal‐Free Route Towards the Synthesis of 1, 2, 3‐Triazoles from Readily Available Primary Amines and Ketones. Issue 25 (June 2016) - Thomas, Joice; Jana, Sampad; John, Jubi; Liekens, Sandra; Dehaen, Wim
Abstract: An unprecedented selective preparation of 1, 5‐disubstituted 1, 2, 3‐triazoles from readily available primary amines, enolizable ketones and 4‐nitrophenyl azide as a renewable source of dinitrogen is developed.